Compliant mechanisms : design of flexure hinges - Lobontiu, Nicolae (Boca Raton, FL : CRC Press, 2021)
"The second edition of Compliant Mechanisms: Design of Flexure Hinges provides practical answers to the design and analysis of devices that incorporate flexible hinges"--
OCLC-licensed vendor bibliographic record.
Keywords: Mechanical movements -- Design and construction; Hinges -- Design and construction; TECHNOLOGY / Engineering / Mechanical; TECHNOLOGY / Industrial Design / General